PENGARUH PELATIHAN KUESIONER PRA SKRINING PERKEMBANGAN (KPSP) TERHADAP TINGKAT PENGETAHUAN DAN KETERAMPILAN KADER POSYANDU - Nurlaili, Riftiani Nikmatul (Jurnal Ilmiah Bidan (JIB), 2021)
Abstract Cadres has a role in the early detection of premature infantile growth deviation based on Deteksi Dini Tumbuh Kembang (DDTK) which contains Kuesioner Pra Skrining Perkembangan (KPSP). The results of preliminary study, posyandu cadres of Wonokromo Village have not been able to monitor the development of infants and toddlers using KPSP. Thus, posyandu cadres require KPSP training. This training aims to analyze the effect of KPSP training on improving knowledge and skills of posyandu cadres in monitoring the development of children under five. The research method is pre experiment one group pre test-post test. The sample of the research are 40 female cadres with age range 35-60 years old. The training was conducted in November 2017 in Wonokromo Village. Training methods include lectures, discussions, and role plays. The knowledge and skills of the cadres using KPSP were assessed from the total score of the answers. The knowledge level was analyzed using Wilcoxon signed rank test and skill level using Paired t-test. The majority of the sample have high school education level, have followed posyandu last 3 months, and have never received KPSP training. The result of the statistical test on the knowledge level shows the mean difference of 4.13 (p=0,000; 95% CI 3.50-4.75). The result of statistical test at the skill level shows the mean difference of 7.43 (p = 0,000; 95% CI 6,48-8,37). Thus there is a significant influence between KPSP training on improving the knowledge and skills of posyandu cadres in monitoring the development of children under five. Keywords: KPSP, knowledge, Posyandu cadres, skills, training